2018
DOI: 10.1186/s13075-018-1693-x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human proteoglycan-4 reduces phagocytosis of urate crystals and downstream nuclear factor kappa B and inflammasome activation and production of cytokines and chemokines in human and murine macrophages

Abstract: BackgroundGout is an inflammatory arthritis caused by monosodium urate monohydrate (MSU) crystals’ joint deposition. MSU phagocytosis by resident macrophages is a key step in gout pathogenesis. MSU phagocytosis triggers nuclear factor kappa B (NFκB) activation and production of cytokines and chemokines. Proteoglycan-4 (PRG4) is a glycoprotein produced by synovial fibroblasts and exerts an anti-inflammatory effect in the joint mediated by its interaction with cell surface receptor CD44. PRG4 also binds and anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
75
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 54 publications
(81 citation statements)
references
References 69 publications
6
75
0
Order By: Relevance
“…Bone marrow-derived macrophages (BMDMs) from CD44 wild-type animals (Cd44 +/+ ) appeared to internalize MSU crystals to a greater extent when compared to the CD44 knockout (Cd44 −/− ) animals (white arrows point to MSU crystals in DAPI-stained BMDMs; Figure 1D). This observation is consistent with the phagocytic role of the CD44 receptor and validates our earlier observations that PRG4, a CD44 ligand, prevents MSU phagocytosis by macrophages [33]. Using flow cytometry to detect MSU phagocytosis via a change in macrophage cell side-scatter [33], we observed that the CD44 receptor-ligand, HA, significantly reduced MSU phagocytosis by THP-1 macrophages.…”
Section: Characterization Of Cd44 Receptor Expression On Macrophagessupporting
confidence: 91%
See 4 more Smart Citations
“…Bone marrow-derived macrophages (BMDMs) from CD44 wild-type animals (Cd44 +/+ ) appeared to internalize MSU crystals to a greater extent when compared to the CD44 knockout (Cd44 −/− ) animals (white arrows point to MSU crystals in DAPI-stained BMDMs; Figure 1D). This observation is consistent with the phagocytic role of the CD44 receptor and validates our earlier observations that PRG4, a CD44 ligand, prevents MSU phagocytosis by macrophages [33]. Using flow cytometry to detect MSU phagocytosis via a change in macrophage cell side-scatter [33], we observed that the CD44 receptor-ligand, HA, significantly reduced MSU phagocytosis by THP-1 macrophages.…”
Section: Characterization Of Cd44 Receptor Expression On Macrophagessupporting
confidence: 91%
“…This observation is consistent with the phagocytic role of the CD44 receptor and validates our earlier observations that PRG4, a CD44 ligand, prevents MSU phagocytosis by macrophages [33]. Using flow cytometry to detect MSU phagocytosis via a change in macrophage cell side-scatter [33], we observed that the CD44 receptor-ligand, HA, significantly reduced MSU phagocytosis by THP-1 macrophages. Figure 1E depicts the representative flow cytometry plots of MSU-treated macrophages in the absence or presence of HA (100 µg/mL).…”
Section: Characterization Of Cd44 Receptor Expression On Macrophagessupporting
confidence: 91%
See 3 more Smart Citations